STRIAE GRAVIDARUM: RISK FACTORS, PREVENTION, AND MANAGEMENT: A SYSTEMATIC REVIEW - Jani Sari Dabukke, Yeyen (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Objective: Striae Gravidarum (SG) is one of the most prevalent skin disorders in pregnancy. The pathogenesis of SG involves complex hormonal changes. The effect of SG could deteriorate the aesthetic and psychological function in pregnant women. In spite of that, a review of the risk factors, prevention, and treatment of SG is lacking. Therefore, this literature is aimed to summarize the risk factors, prevention, and treatment in order to reduce the incidence and negative impact of SG in pregnant women.Materials and methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, Google Scholar) and included articles published between 2018–2023. Duplicate publications, review articles, and incomplete articles were excludedResults: Database search yielded 2461 articles, which were systematically eliminated, leaving 6 relevant articles. Analyzed articles showed the association between diabetes mellitus and hidradenitis suppurativa.Conclusion: BMI, height, sedentary lifestyle, consumption of milk, eggs, and lower back pain were the risk factors for SG. Studies support the use of olive oil in the treatment and prevention of SG. Certain local herbs are also useful to prevent SG.